PECTIN BEADS IN DRUG DELIVERY: EXTRACTION, FORMULATION, AND PHARMACEUTICAL APPLICATIONS - MUNIYANDY, SARAVANAN (International Journal of Applied Pharmaceutics, 2025)
Pectin is a natural, non-toxic biopolymer derived from plant cell walls, where it constitutes approximately one-third of the dry weight in most higher plants. Predominantly concentrated in the middle lamella, it has traditionally been used in the food industry for its thickening, gelling, and stabilizing properties. However, its unique resistance to gastric and intestinal enzymatic degradation, coupled with fermentability by colonic bacteria, has led to its emerging role in pharmaceutical applications, particularly in targeted drug delivery. The gelling characteristics of pectin depend on its source, molecular weight, and degree of esterification (DE), factors that influence its suitability as a carrier for bioactive agents. Despite the increasing interest in pectin-based systems, previous reviews have largely focused on its conventional uses, lacking depth in recent advancements within pharmaceutical and biomedical domains. This review addresses those lacunae by offering an updated and detailed examination of pectin's pharmaceutical relevance, with a special focus on pectin beads (PB). It outlines the complete process for preparing the PB formulation, including solution preparation, incorporation of active agents, cross-linking, droplet optimization, hardening, washing, and drying. Furthermore, the article examines the gelation and swelling properties of PB, as well as their morphological and physicochemical characterization using scanning electron microscopy (SEM) and zeta potential analysis. Emphasis is placed on their versatile pharmaceutical applications, such as regulated drug release, colon-specific delivery, iron supplementation, immunization, and enhanced stability via polymeric coatings like chitosan and alginate. By synthesizing current findings, this review provides a comprehensive resource for researchers investigating the potential of pectin in modern therapeutic systems.